2018
DOI: 10.1186/s12909-018-1365-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of smoking behavior with lifestyle and mental health among Japanese dental students

Abstract: Background Smoking is a major risk factor for cancer and cardiovascular disease. However, mental stress leads to smoking in dental students. We believe that dentists, as health professionals, should set an example for the public. Therefore, this study determined the prevalence of and factors associated with regular smoking among Japanese dental students. We also surveyed their attitudes regarding smoking cessation and how to counsel smokers about quitting. Methods We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
18
1
Order By: Relevance
“…Non-smokers’ support for the ban on tobacco use in public spaces was in agreement with previous observations from other countries [ 40 , 41 , 42 ]. Similar results were shown by Warren et al [ 14 ], although other studies found that non-smokers presented a higher level of awareness regarding tobacco control [ 22 , 23 , 36 , 43 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Non-smokers’ support for the ban on tobacco use in public spaces was in agreement with previous observations from other countries [ 40 , 41 , 42 ]. Similar results were shown by Warren et al [ 14 ], although other studies found that non-smokers presented a higher level of awareness regarding tobacco control [ 22 , 23 , 36 , 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Cigarettes can also be used to control stress connected with classes and exams, which is presumed to be a reason for a smoking habit [ 20 , 35 ]. Eating out frequently, which is typical for students, is associated with a higher probability to become a smoker [ 36 ]. Furthermore, it has been found that as many as two-thirds of young tobacco users have at least one smoking relative, making a family background a relevant factor of a smoking habit.…”
Section: Discussionmentioning
confidence: 99%
“…This is an alarming result, as both study groups of dental students presented a smoking incidence higher than the general Egyptian population [ 42 ] and Egyptian medical students [ 43 ], and ranked among the highest rates worldwide [ 3 , 44 ]. In contrast to student groups in Japan [ 45 ], India [ 46 ], and Germany [ 3 ], the current survey displayed higher smoking rates among preclinical than clinical participants. This observation was explained in previous studies on medical and dental students, as higher levels of education or clinical knowledge were positively correlated with a cessation of tobacco-associated habits or the consumption of other psychoactive substances [ 47 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 82%
“…The findings showed that the rates of smoking rates ranged widely, from 2%-31% for doctors and 2%-41% for nurses depending on the country studied and the criteria used. Related factors such as sex, age, profession, and health behaviors/lifestyles (such as alcohol use, skipping breakfast, general health and poor sleep) were found to be significantly associated with smoking (11,(15)(16)(17). Additionally, several studies also showed a significant association between smoking behavior and burnout among healthcare workers in Italy (18), and physicians and nurses in Saudi Arabia (19).…”
Section: Introductionmentioning
confidence: 99%